S100A11 plays a role in homologous recombination and genome maintenance by influencing the persistence of RAD51 in DNA repair foci. Issue 20 (17th October 2016) - Foertsch, Franziska; Szambowska, Anna; Weise, Anja; Zielinski, Alexandra; Schlott, Bernhard; Kraft, Florian; Mrasek, Kristin; Borgmann, Kerstin; Pospiech, Helmut; Grosse, Frank; Melle, Christian
ABSTRACT: The repair of DNA double-strand breaks (DSBs) by homologous recombination (HR) is an essential process in maintenance of chromosomal stability. A key player of HR is the strand exchange factor RAD51 whose assembly at sites of DNA damage is tightly regulated. We detected an endogenous complex of RAD51 with the calcium-binding protein S100A11, which is localized at sites of DNA repair in HaCaT cells as well as in normal human epidermal keratinocytes (NHEK) synchronized in S phase. In biochemical assays, we revealed that S100A11 enhanced the RAD51 strand exchange activity. When cells expressing a S100A11 mutant lacking the ability to bind Ca 2+, a prolonged persistence of RAD51 in repair sites and nuclear γH2AX foci was observed suggesting an incomplete DNA repair. The same phenotype became apparent when S100A11 was depleted by RNA interference. Furthermore, down-regulation of S100A11 resulted in both reduced sister chromatid exchange confirming the restriction of the recombination capacity of the cells, and in an increase of chromosomal aberrations reflecting the functional requirement of S100A11 for the maintenance of genomic stability. Our data indicate that S100A11 is involved in homologous recombination by regulating the appearance of RAD51 in DSB repair sites. This function requires the calcium-binding activity of S100A11.